Pengaruh Konsumsi dan Investasi terhadap Tingkat Pengangguran Terbuka di Kalimantan Barat Periode 1995-2024 - Sirly Nur Amelia; M. Afdal Samsuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study investigates the impact of household consumption and investment on the open unemployment rate in West Kalimantan over both short and long terms. Using time series data from 1995–2024 and employing the Vector Error Correction Model (VECM) in EViews 12, results show all variables become stationary after first differencing. Johansen cointegration confirms a long-run equilibrium relationship. VECM findings reveal that investment significantly increases unemployment in the long run, while household consumption has no significant effect. In the short term, a significant error correction mechanism exists, indicating adjustment toward long-run equilibrium. Diagnostic tests confirm model validity through absence of autocorrelation and normally distributed residuals. These results highlight the need for more targeted policies to reduce unemployment.